The Influence of the Cu-Al2O3 Ratio of the Receiving Tube in a 50 MW Hybrid Solar Plant - Guillermo Benítez-Olivares; Alejandro Torres-Aldaco; Raúl Lugo-Leyte; José Javier Valencia-López; Luis Alberto Romero-Vázquez; Helen D. Lugo-Méndez (Energies)
Direct steam generation (DSG) is a promising technology for introducing solar energy into industrial applications, yet it still faces significant challenges. This work analyzes two critical issues associated with DSG: temperature gradients on the receiver tube wall caused by direct and concentrated radiation and flow instability resulting from the phase transition of the working fluid from liquid–vapor to vapor. These phenomena can reduce the mechanical strength of the receiver tube and lead to sudden pressure increases, deformation, or rupture, which hinder the implementation of DSG in solar thermal plants. To address these challenges, the behavior of a receiver tube composed of copper on the inside and an Al2O3 envelope is studied. A 50 MWe hybrid solar thermal plant is proposed for Mulegé, Baja California Sur, Mexico, including a solar field designed to analyze the production of superheated steam during peak solar irradiance hours. The effect of the Cu-Al2O3 ratio on the receiver tube is evaluated, with Al2O3 serving as a thermal regulator to reduce temperature gradients and mitigate flow instability. This combination of materials improves the receiver tube’s performance, ensuring mechanical stability and enhancing the viability of DSG systems. By reducing temperature gradients and flow instability, DSG-based plants can double thermal efficiency and significantly lower environmental impact by eliminating the need for thermal oils, which require frequent replacement. These findings demonstrate the potential for hybrid solar thermal plants to provide sustainable and efficient solutions for industrial energy needs.